2007
DOI: 10.1007/s11102-007-0003-4
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic panhypophysitis in a young man with involvement of the cavernous sinus and clivus

Abstract: Lymphocytic hypophysitis is an unusual inflammatory lesion that is caused by autoimmune destruction of the pituitary gland. We report a case of 42-year-old man who presented with a 6-month history of severe headache, blurred vision in the right eye, hearing loss, polyuria, polydipsia, and impotence. Medical history showed that he and his mother had osteopetrosis. The results of the physical examination and laboratory tests showed that secondary hypothyroidism, hypogonadism, and hypocortisolism had developed. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
0
12
0
5
Order By: Relevance
“…41 Therefore, the parasellar T2 dark sign is more suitable for LYH that infiltrates around the pituitary. Some previous studies have reported cavernous involvement in patients with LYH, 5,6,10,[42][43][44][45][46] but no studies have mentioned the parasellar T2 dark sign.…”
Section: Discussionmentioning
confidence: 96%
“…41 Therefore, the parasellar T2 dark sign is more suitable for LYH that infiltrates around the pituitary. Some previous studies have reported cavernous involvement in patients with LYH, 5,6,10,[42][43][44][45][46] but no studies have mentioned the parasellar T2 dark sign.…”
Section: Discussionmentioning
confidence: 96%
“…17 T2-weighted and fat-suppressed sequences are also useful, specifically in the search of clival bone marrow edema, which has been reported in some cases of hypophysitis, 31 but these sequences are not routinely performed and thus could not be included in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Very few cases of LYH have been reported previously in association with ON, and each of those patients presented with CDI initially, was diagnosed with a subtype of LYH, and later developed ON [4][5][6]. There is one case report of a middle-aged man with LIPH presenting with multiple progressive symptoms who initially had unilateral blurry vision four months prior that spontaneously resolved in a few weeks, and while the publication appears to attribute the patient's visual symptoms to optic chiasmal involvement as seen on MRI, these images were not obtained until months after his vision returned [7]. In the case of our patient, the imaging and clinical findings at the time of initial presentation confirm that the initial diagnosis was ON rather than visual loss from compression of the optic apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…The mainstay of treatment for LYH is medical, including hormone replacement and immunosuppression with corticosteroids [1,2,[7][8][9], although steroid-unresponsive disease has been described and may be treated with other drugs or radiation therapy [1,7,8,10]. Surgical resection (typically via a transsphenoidal approach) may be required in cases of substantial mass effect on the optic apparatus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation